Cognitive factors involved in delusion formation - Nieznański, Marek (Studia Psychologica: Theoria et praxis, 2003)
The paper presents major cognitive hypotheses of delusion formation and maintenance. Relevant findings of empirical studies of attentional bias, ‘theory of mind’ deficits, probabilistic reasoning biases, and self-serving causal attributions in people with delusions are reviewed. Some limitations to existing research are discussed.